Analysis of Technical Efficiency of Small-Scale Rice Farmers in Indonesia - Wardana, Fitri; Yamamoto, Naoyuki; Kano, Hideyuki (Journal of Tropical Life Science, 2018)
In this study, we analyzed the performance of small-scale rice farmers who used hand tractors in Jember Regency, Indonesia. Data were collected from 144 small-scale rice farmers in six districts through the use of a questionnaire in September 2015. The Data Envelopment AnalysisSlack-Based Model (DEA-SBM) was used to calculate the technical efficiency of small-scale rice farmers based on seven inputs and one output by determining Overall Technical Efficiency (OTE), Pure Technical Efficiency (PTE), and Scale Efficiency (SE). The results showed that out of 144 small-scale rice farmers, only nine farmers and 14 farmers were evaluated as strongly efficient and weakly efficient, respectively, while the rest were categorized as inefficient. The average values for OTE, PTE, and SE were 0.41, 0.63, and 0.61, respectively. The observed inefficiency was because of both poor input utilization (managerial inefficiency) and failure to operate at an optimal scale (scale inefficiency). Such analysis of technical efficiency can encourage small-scale rice farmers to enhance their performance and profitability.